2007
DOI: 10.1007/s00774-007-0766-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IL-23 and IL-27 on osteoblasts and osteoclasts: inhibitory effects on osteoclast differentiation

Abstract: Interleukin (IL)-23 and IL-27 are IL-6/IL-12 family members that play a role in the regulation of T helper 1 cell differentiation. Cytokines are known to be involved in the bone remodeling process, although the effects of IL-23 and IL-27 have not been clarified. In this study, we examined the possible roles of these cytokines on osteoblast phenotypes and osteoclastogenesis. We found that IL-27 induced signal transducers and activators of transcription 3 activation in osteoblasts. However, neither IL-23 nor IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
54
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 36 publications
7
54
2
Order By: Relevance
“…These results are in contrast to a report of reduced osteoclast formation upon IL-23 treatment of bone marrow macrophages [48]. This may relate to a difference in expression of IL-23 receptor on BMM derived from the ddY mouse strain as the authors were unable to detect the protein by Western blotting.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results are in contrast to a report of reduced osteoclast formation upon IL-23 treatment of bone marrow macrophages [48]. This may relate to a difference in expression of IL-23 receptor on BMM derived from the ddY mouse strain as the authors were unable to detect the protein by Western blotting.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it is plausible that an increase in the percentage of precursor cells expressing RANK even under conditions of baseline levels of RANKL could result in enhanced osteoclastogenesis. Further in vivo studies are needed to clarify this issue.These results are in contrast to a report of reduced osteoclast formation upon IL-23 treatment of bone marrow macrophages [48]. This may relate to a difference in expression of IL-23 receptor on BMM derived from the ddY mouse strain as the authors were unable to detect the protein by Western blotting.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…By contrast, a recent study found that IL-27 could be beneficial by inhibiting osteoclastogenesis [19]. This study corroborates the findings of other ones that consider IL-27 to be an anti-inflammatory factor [20] and a possible positive inflammatory regulator in arthritis [21], multiple sclerosis [22], and even cancer [23].…”
Section: Discussionsupporting
confidence: 89%